Launching Successful Beginnings for Early Career Faculty Researchers. (February 2018) - Conn, Vicki S.; Anderson, Cindy M.; Killion, Cheryl; Bowers, Barbara J.; Wyman, Jean F.; Herrick, Linda M.; Zerwic, Julie J.; Smith, Carol E.; Cohen, Marlene Z.; Benefield, Lazelle E.; Topp, Robert; Fahrenwald, Nancy L.; et al.
Junior faculty follow a research path replete with challenges as they strive to create knowledge in their area of interest while balancing new responsibilities. Unlike graduate school, where students focus inward on personal development, junior faculty must add responsibilities in ways that hold them accountable as members of a university. This special article deals with three themes of interest to new junior faulty launching research programs: personal development, collaboration and team development within university settings, and funding advice. Strategies in these areas provide guidance on navigating early careers and finding success in the academic setting.